Development module of post-flood Islamic psychotherapy based on the maqasid syari’ah concept / Norazmi Anas ... [et al.] - Anas, Norazmi; Mod Noor, Mohd Syukri; Zulkipli, Shahril Nizam; Aziz, Nurul Hidayah; Mohd. Yaacob, Hamdi Rahman; Muhamad Ramlan, Anaztasia Natasha (2017)
Flooding is a major contributing factor in the increment of the emotional and psychological problems such as fear, trauma, loss of property and lives having both short and long term effects. Several measures have been identified as an approach to overcome these problems which are through emotional support, positive evaluation and self-reflection, religious approach and acceptance of reality comprises coping strategies and social support. This paper aims to expose the concept, significance and proposals for the post-flood Islamic psychotherapy development module based on the maqasid syari’ah concept. It started with the production model of post-flood Islamic psychotherapy that will be applied to become a module for the usage of local community in Malaysia.